2022
DOI: 10.1002/hec.4611
|View full text |Cite
|
Sign up to set email alerts
|

Omnibus or Ominous immigration laws? Immigration policy and mental health of the Hispanic population

Abstract: Since the passage of the 1986 Immigration Reform and Control Act (IRCA) that tried to curb unauthorized immigration in the U.S., a number of states passed single immigration laws to control unauthorized immigration. Such laws (e.g., 287(g) agreements with the U.S. Immigration and Customs Enforcement, E-Verify mandates, Secure Communities (SC) program) started to be implemented in the 2000s and studies (e.g., Bohn et al., 2014;Kostandini et al., 2014) find that they have decreased the share of non-citizen Hispa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…SB1070 empowers local law enforcement to detain any person who is suspected of having ‘unlawful’ immigration status. A growing body of quantitative literature has begun investigating the impact of such laws on mental health [49,55–57,58 ▪ ], though a lack of robust measures of mental health are a common limitation of this literature. Using data from the biennial Youth Risk Behavioral Surveillance System, investigators found evidence of increased reported past-day sadness for Hispanic students in Arizona ( n = 3402) following the enactment of SB1070, relative to Hispanic students in other states ( n = 64 225) [58 ▪ ].…”
Section: Criminalization Of Immigrationmentioning
confidence: 99%
“…SB1070 empowers local law enforcement to detain any person who is suspected of having ‘unlawful’ immigration status. A growing body of quantitative literature has begun investigating the impact of such laws on mental health [49,55–57,58 ▪ ], though a lack of robust measures of mental health are a common limitation of this literature. Using data from the biennial Youth Risk Behavioral Surveillance System, investigators found evidence of increased reported past-day sadness for Hispanic students in Arizona ( n = 3402) following the enactment of SB1070, relative to Hispanic students in other states ( n = 64 225) [58 ▪ ].…”
Section: Criminalization Of Immigrationmentioning
confidence: 99%